Maxicircle architecture and evolutionary insights into Trypanosoma cruzi complex. - Luisa Berná (Public Library of Science (PLoS), 2021)
We sequenced maxicircles from T. cruzi strains representative of the species evolutionary diversity by using long-read sequencing, which allowed us to uncollapse their repetitive regions, finding that their real lengths range from 35 to 50 kb. T. cruzi maxicircles have a common architecture composed of four regions: coding region (CR), AT-rich region, short (SR) and long repeats (LR). Distribution of genes, both in order and in strand orientation are conserved, being the main differences the presence of deletions affecting genes coding for NADH dehydrogenase subunits, reinforcing biochemical findings that indicate that complex I is not functional in T. cruzi. Moreover, the presence of complete minicircles into maxicircles of some strains lead us to think about the origin of minicircles. Finally, a careful phylogenetic analysis was conducted using coding regions of maxicircles from up to 29 strains, and 1108 single copy nuclear genes from all of the DTUs, clearly establishing that taxonomically T. cruzi is a complex of species composed by group 1 that contains clades A (TcI), B (TcIII) and D (TcIV), and group 2 (1 and 2 do not coincide with groups I and II described decades ago) containing clade C (TcII), being all hybrid strains of the BC type. Three variants of maxicircles exist in T. cruzi: a, b and c, in correspondence with clades A, B, and C from mitochondrial phylogenies. While A and C carry maxicircles a and c respectively, both clades B and D carry b maxicircle variant; hybrid strains also carry the b- variant. We then propose a new nomenclature that is self-descriptive and makes use of both the phylogenetic relationships and the maxicircle variants present in T. cruzi.